2009
DOI: 10.1063/1.3072828
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of Cr-doped diamond-like carbon

Abstract: Chromium-doped hydrogenated diamond-like carbon ͑Cr-DLC͒ and chromium carbide hydrogenated DLC alloys were synthesized by plasma-assisted vapor deposition and investigated by x-ray absorption near edge structure spectroscopy, extended x-ray absorption fine structure, and superconducting quantum interference device ͑SQUID͒ magnetometry. Structural and magnetic properties of the doped and alloy materials were investigated as a function of the Cr concentration ͑0.1-20 at. %͒. Toward the upper end of the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Further calculations were performed for the supercells consisting of 1, 3, 4, and 6 Cr ions yielding the atomic concentrations of 1.5625, 4.6875, 6.25, and 9.375 at.% at which the presence of low-temperature ferromagnetism was observed experimentally [4]. We determined the total energies for the non-spin-polarized and the spin-polarized case.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Further calculations were performed for the supercells consisting of 1, 3, 4, and 6 Cr ions yielding the atomic concentrations of 1.5625, 4.6875, 6.25, and 9.375 at.% at which the presence of low-temperature ferromagnetism was observed experimentally [4]. We determined the total energies for the non-spin-polarized and the spin-polarized case.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Ni-DLC films may find usage in optoelectronics and in magnetic devices [30,31,36,37]. It is possible to control the size of incorporated metal particles inside DLC matrix [36,37]. We expect that the magnetic properties of the films can be tailored by manipulation of the size of metal particles.…”
Section: Introductionmentioning
confidence: 97%
“…Although few groups have studied magnetic properties of DLC and metal doped DLCs but we are not aware of any magnetic characterizations of electrodeposited Ni-DLC thin films yet. Colon Santana et al [36] reported magnetism studies of chromium (Cr) doped DLC thin films synthesized by plasma assisted vapor deposition method. They found that Cr doped DLC thin films exhibited ferromagnetic property at very low temperatures, whereas Cr 3 C 2 clusters appeared to be antiferromagnetic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, recent developments in a-C materials with favorable magnetoelectronic properties have attracted attention. [11][12][13][14][15] with a graphitic C matrix, 16 the chemical bonding between the p-shell of carbon atoms and metallic cobalt atoms at the cluster surface can strongly influence the physical properties of such a material. These facts reveal that interface intermixing can dramatically influence magnetic measurements and lead to erroneous conclusions.…”
mentioning
confidence: 99%